Role of CRF1 and CRF2 receptors in the lateral hypothalamus in cardiovascular and anxiogenic responses evoked by restraint stress in rats: Evaluation of acute and chronic exposure - Barretto-de-Souza, Lucas [UNESP] (2022)
We investigated the role of corticotropin-releasing factor (CRF) neurotransmission within the lateral hypothalamus (LH) in cardiovascular and anxiogenic-like responses evoked by acute and repeated restraint stress in rats. For this, animals were subjected to intra-LH microinjection of a selective CRF1 (CP376395) or CRF2 (antisauvagine-30) receptor antagonist before either an acute or the 10th session of restraint stress. Restraint-evoked arterial pressure and heart rate increases, tail skin temperature decrease and anxiogenic-like effect in the elevated plus maze (EPM) were evaluated. We also assessed the effect of 10 daily sessions of restraint on expression of CRF1 and CRF2 receptors within the LH. We identified that antagonism of either CRF1 or CRF2 receptor within the LH decreased the tachycardia during both the acute and 10th session of restraint, but the effect of the CRF1 receptor antagonist was more pronounced during the 10th session. Acute restraint stress also caused anxiogenic-like effect, and this response was inhibited in animals treated with either CP376395 or antisauvagine-30. Anxiety-like behaviors were not changed following the 10th session of restraint, and pharmacological treatments did not affect the behavior in the EPM in chronically stressed animals. Repeated restraint also did not change the level of the CRF receptors within the LH. Taken together, the findings indicate that CRF1 and CRF2 receptors within the LH are involved in tachycardic and anxiogenic-like responses to aversive stimuli. Control of tachycardia by the CRF1 receptor is sensitized by previous stressful experience, and this effect seems to be independent of changes in expression of the receptor.